Implementasi Pembelajaran Berdiferensiasi Mata Pelajaran IPS SMP Kelas 7 Materi Keberagaman Lingkungan Sekitar - Muttaqin, Aqiq (Proceedings Series on Social Sciences & Humanities, 2023)
This study aims to observe the implementation of differentiated learning in the subject of social studies for 7th-grade students with a focus on the topic of environmental diversity. The observation was conducted in two groups, where one group was given conventional teaching methods and the other group received differentiated teaching methods. In the differentiated learning group, the teacher provided different tasks to students based on their abilities and interests. Additionally, the teacher used technology in teaching by providing videos or e-books tailored to students learning needs. The results showed that students in the differentiated learning group were more actively involved in learning compared to those in the conventional learning group. This was evident in the level of participation in class discussions and the students’ eagerness to complete the given tasks. Furthermore, there was a significant difference in the learning abilities and interests of the students, so the tasks given were customized according to their specific needs. Based on the observation results, it can be concluded that the implementation of differentiated learning in social studies for 7th-grade students with a focus on the topic of environmental diversity can improve the quality of teaching and student learning outcomes. Differentiated learning provides an opportunity for students to learn according to their abilities and interests, which can increase their motivation to learn and help them achieve their full learning potential. Furthermore, the use of technology in teaching can also enhance the effectiveness of differentiated learning. Teachers can provide learning resources tailored to the students’ needs, such as videos or e-books that can be accessed anytime and anywhere. This can help students learn independently and increase the efficiency of learning. However, the implementation of differentiated learning also poses challenges, such as the time and resources needed to prepare different tasks for each student. Therefore, teachers need to conduct regular observations of the learning abilities, interests, and needs of their students and provide constructive feedback to help students improve and enhance their learning abilities.